It is not the ideology but the resources: family language policy in a comparative perspective. Issue 9 (21st October 2022) - Yagmur, Kutlay; Bohnacker, Ute
ABSTRACT: This Special Issue focuses on family language policy as part of the language maintenance and shift efforts of Turkish heritage-speaker families in Australia, Belgium, France, Sweden and the Netherlands.